KOMITMEN ORGANISASI DAN TURNOVER INTENTION KARYAWAN HOTEL MELAWAI - Pramanik, Purwanti Dyah; Festivalia, Filma; Adawiyah, Robiatul (Jurnal Ilmiah Pariwisata, 2017)
Hotel industries has high turnover. Employees’ leaving would impact some problems such as lack of employees, cost of recruitment, training cost of new employees, inefficiencies, and productivity decreases. The factors of employees’ turnover are the improvement of employees’ turnover intention. This would increase because of the absence of organizational commitment. Organizational commitment includes value commitment, effort commitment, and retention commitment. The study aimed to analyze the impact of organizational commitment to employees’ turnover intention. The method was quantitative descriptive. It used cross-sectional. The data was collected by distributing questionaires. The respondents were the employees of hotel Melawai in Jakarta. The respondents were chosen by accidental sampling. Data analysis were validity and reliability test, descriptive analysis, Pearson correlation, and simple linear regression by using SPSS 21 for window software. The result of the research indicated that organizational commitment which consisted of value commitment, effort commitment, and retention commitment influenced employees’ turnover intention negatively and significantly. It meant that the higher organizational commitment would be the lower turnover intention of hotel Melawai employees in Jakarta.